Critical Thinking Profile in Coding Learning for 6-Year-Old Early Childhood Education Students - Darwati Darwati; Yes Matheos Lesarus Malaikosa; Rachma Hasibuan; Nurul Istiq’faroh; Andi Kristanto; Sayhidul Haq (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The rapid digitalization era has positioned coding as a crucial medium for developing foundational cognitive skills in early childhood. Specific Background: For 6-year-old learners, visual-based coding activities offer opportunities to strengthen logical reasoning and structured problem-solving, yet empirical descriptions of their critical thinking profile remain limited. Knowledge Gap: Existing studies rarely document how critical thinking indicators manifest during coding activities in early childhood settings. Aims: This study aims to analyze the critical thinking profile of 6-year-old children engaged in coding learning at TK Tunas Harapan. Results: Findings show that coding activities significantly enhance children’s analytical, evaluative, and problem-solving abilities, reflected in notable score improvements across learning cycles, although 40% of students initially demonstrated difficulties in critical thinking. Novelty: This research provides early evidence on how coding education concretely stimulates critical thinking in young children within rural early childhood contexts. Implications: The results highlight the importance of integrating developmentally appropriate coding activities into early childhood curricula to strengthen critical thinking foundations and inform future digital learning model development for PAUD. Highlights: Coding learning significantly strengthens critical thinking skills in 6-year-old children. Visual-based coding activities help improve analysis, evaluation, and problem-solving abilities. Integrating coding in early childhood supports digital literacy and cognitive readiness in the digital era. Keywords: Critical Thinking, Coding Education, 6-year-old Children, Digitalization, Early Childhood Education